Change of coverage and land use in coastal plain associated with anthropogenic processes: case San Blas, Nayarit - Nájera González, Areli; Carrillo González, Fátima Maciel; Morales Hernández, Julio César; Nájera González, Oyolsi (Instituto de Ecología, A.C., 2021)
The changes in land use generated by the development of human activities have accelerated the loss of vegetation cover. Due to its location on coastal plains, mangrove coverage has been one of the most affected in recent years. The main changes have been made evident by aquaculture, agriculture, and tourism. The loss of mangrove swamps entails changes in the climate at the local scale, which affects variations in the water cycle and the saline balance of the coastal lagoons, inciting a domino effect on biodiversity, soils, and therefore economic activities. The objective of this work was to evaluate the change in coverage and land use of the coastal plain of San Blas, Nayarit from the period 2000-2019 and its trend for 2038. The method used was the supervised classification of satellite images in a GIS and the Markov chains tool for future projection. An increase in areas for shrimp farming was found (4.3%), which led to the displacement of flood zones, possible associated with impacts on the hydrologic system, causing a reduction in mangrove cover (4.7%), however, it is expected that the trend will continue to a lesser extent up to 2038. This conclusion is expected to be a reference for future decisions on the development of anthropogenic activities in this area and others in the coastal plain.